One. - Kaur Gill, Caryn. (2008)
One is a book, which highlights the unique wedding celebrations that take place within various races and religions in Singapore - namely Chinese, Malay, Hindus and Sikh. The 68 photographs in our book encompasses the mental, emotional and physical union that takes place during a wedding.